PAN/PEG and PAN/n-Alkane Nanofibers Suitable For Heat Storage Applications in Textiles - Önder Karaoğlu, Emel; Nergis, Fatma Banu; SARIER, NİHAL; ARAT, REFİK (My University, 2018)
Production of shell/core structured nanowebs were performed via Yflow® coaxial electrospinning device. Polyacrylonitrile (PAN) was chosen as a shell material considering its good thermal properties as well as suitability for textile applications. Two types of PCMs which were polyethyleneglycols (PEGs) and n-alkanes were chosen to use as core materials because of their high latent heat capacities, thermal stabilities and ecologically friendly properties. Two different concentrations which were 4wt% and 6wt% of PAN in dimethylacetamide (DMAc) used as a shell. 40wt% and 30wt% solutions of PEG400 and PEG600 in DMAc and 100wt% of n-pentadecane and n-hexadecane used as core. Experiments was carried out with 15 cm collector distance at voltage value around 12-14 kV and 10 nanowebs with different PAN/PCM compositions were produced. Structural characterizations of the produced nanowebs were conducted with fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). Diameter distribution analysis also performed by ImageJ-DiameterJ program. The thermal properties of the samples were determined using differential scanning calorimetric (DSC) analyses. Also conductivity and viscosity analyses were performed at room temperature for core and shell solutions.
Keywords: Tekstil